Preparation method of natural latex synergistic lignin biological adhesive
Through graft modification technology, natural latex and lignin are combined to prepare high-performance environmentally friendly bioadhesive, which solves the problem of insufficient performance of existing environmentally friendly adhesives, and reduces the release of harmful substances, achieving environmentally friendly and high-performance adhesives.
Patent Information
- Application Number
- CN202411823750.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-04-18
AI Technical Summary
There are shortcomings in performance of existing environmentally friendly adhesives, and traditional petroleum-based adhesives will release harmful volatile organic compounds during production and use, affecting the environment and human health.
Through graft modification technology, natural latex and lignin are combined to prepare an environmentally friendly bioadhesive agent. The method includes graft polymerization of natural latex with lignin, ammonium persulfate and NaOH solutions to form a high-performance adhesive.
It significantly improves the adhesive strength, water resistance and heat resistance, while maintaining biodegradability and non-toxic properties, reducing environmental pollution.
Smart Images

Figure CN119842364A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of adhesives, and in particular to an environmentally friendly bioadhesive prepared by using natural latex and lignin as raw materials through a grafting modification technology. Background Art
[0002] With the enhancement of environmental awareness and the demand for sustainable development, the development of green, environmentally friendly and high-performance adhesives has become an important research direction in the field of materials science. Although traditional petroleum-based adhesives have excellent performance, they release harmful volatile organic compounds (VOCs) during production and use, posing a potential threat to the environment and human health. In addition, the environmentally friendly adhesives currently used in industry mainly use soy protein or starch as the main raw materials. Since they are derived from food materials, they may compete with people for food. Natural latex and lignin, as biomass resources, show great potential in the preparation of adhesives due to their rich sources, renewability and biodegradability. Therefore, the development of green, environmentally friendly and high-performance environmentally friendly bio-based adhesives has become a research hotspot. Based on this, the present invention provides an environmentally friendly bio-adhesive using natural latex grafted with lignin and a preparation method thereof, aiming to reduce pollution to the environment and improve the comprehensive performance of the adhesive. Summary of the invention
[0003] The purpose of the present invention is to provide an environmentally friendly adhesive based on natural latex, that is, a natural polymer compound composed of polyisoprene as the main component and the rest of which is composed of non-rubber substances such as protein, fatty acid, ash, sugar, etc., and introduced with lignin through a grafting reaction, and at the same time discloses a specific preparation method thereof. The adhesive not only retains the biodegradability and non-toxicity of natural latex, but also significantly improves the bonding strength and water resistance through the introduction of lignin.
[0004] In order to achieve the above object, the present invention provides a method for preparing a natural latex grafted lignin bioadhesive, which is made from the following raw materials: 100 parts of natural latex, 10-50 parts of 15wt% lignin solution, 1 part of 2wt% ammonium persulfate solution, and 50mL of 0-1mol / L NaOH solution.
[0005] The preparation method of the natural latex grafted lignin bioadhesive comprises the following steps:
[0006] Step 1, prepare the 0.1 mol / L NaOH solution: add 2 g NaOH and 50 mL deionized water into a beaker, and stir with a glass rod until fully dissolved;
[0007] Step 2, preparing the 15wt% lignin aqueous solution: 15 parts of lignin dry powder and 85 parts of deionized water are stirred at a speed of 300-330rpm until they are completely dissolved to obtain a uniformly dispersed lignin aqueous solution, and the pH of the lignin aqueous solution is adjusted to 9 using the 0.1mol / L NaOH solution described in step 1;
[0008] Step 3, preparing the 2 wt% ammonium persulfate solution: adding 2 parts of ammonium persulfate and 98 parts of deionized water into a beaker, stirring with a glass rod until dissolved for later use;
[0009] Step 4, preparing a mixed solution of lignin and ammonium persulfate: taking 1 portion of the 2 wt% ammonium persulfate solution in step 3, adding it to the 15 wt% lignin aqueous solution in step 2, stirring at 60±2° C. and 300-330 rpm for 45 min to obtain a mixed solution of lignin and ammonium persulfate;
[0010] Step 5, preparing a natural latex grafted lignin bioadhesive: adding the mixed solution described in step 4 to 100 parts of natural latex, stirring for 3 hours at 60±2°C and 300-330rpm to allow lignin and natural latex to undergo a grafting polymerization reaction. After the reaction is completed, unreacted macromolecular impurities are removed by filtration or centrifugation to obtain a pure adhesive product.
[0011] Preferably, the weight proportion of lignin in the lignin aqueous solution is 15%.
[0012] Preferably, in step 4, the reaction time of the lignin and the mixed solution of ammonium persulfate is 45 minutes, and the reaction temperature is 60±2°C.
[0013] Preferably, the stirring reaction time in step 5 is 3 hours and the reaction temperature is 60±2°C.
[0014] Preferably, the lignin in step 2 is one or more of alkali lignin, sodium lignin sulfonate, and enzymatic lignin.
[0015] The present invention has at least the following beneficial effects:
[0016] Environmentally friendly and non-toxic: The present invention uses natural latex and lignin as the main raw materials, does not contain harmful substances commonly found in traditional petroleum-based adhesives, is friendly to the human body and the environment, and is safe to use.
[0017] High performance: By grafting lignin, the bonding strength, water resistance and heat resistance of the adhesive are significantly improved.
[0018] Simple process: The preparation process is simple and easy, the raw materials are widely available, and it is easy to produce on a large scale.
[0019] Wide application: It is suitable for wood processing, furniture making, textile printing and dyeing and other fields, and has broad market prospects.
[0020] Other advantages, objectives and features of the present invention will be embodied in part through the following description, and in part will be understood by those skilled in the art through study and practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 This is a flow chart of a method for preparing a natural latex grafted lignin bioadhesive according to the present invention;
[0022] Figure 2 These are photos of the natural rubber latex grafted lignin bioadhesives of Examples 1, 2, and 3 of the present invention. DETAILED DESCRIPTION
[0023] The natural latex (NRL) used in this application was purchased from Dongguan Shunjie Plastic Technology Co., Ltd., with a dry rubber content (DRC) of 60%. The present invention is further described in detail below in conjunction with the accompanying drawings so that those skilled in the art can implement it according to the description.
[0024] Step 1, prepare the 0.1 mol / L NaOH solution: add 2 g NaOH and 50 mL deionized water into a beaker, and stir with a glass rod until fully dissolved;
[0025] Step 2, preparing the 15wt% lignin aqueous solution: 15 parts of lignin dry powder and 85 parts of deionized water are stirred at a speed of 300-330rpm until they are completely dissolved to obtain a uniformly dispersed lignin aqueous solution, and the pH of the lignin aqueous solution is adjusted to 9 using the 0.1mol / L NaOH solution described in step 1;
[0026] Step 3, preparing the 2 wt% ammonium persulfate solution: adding 2 parts of ammonium persulfate and 98 parts of deionized water into a beaker, stirring with a glass rod until dissolved for later use;
[0027] Step 4, preparing a mixed solution of lignin and ammonium persulfate: taking 1 portion of the 2 wt% ammonium persulfate solution in step 3, adding it to the 15 wt% lignin aqueous solution in step 2, stirring at 60±2° C. and 300-330 rpm for 45 min to obtain a mixed solution of lignin and ammonium persulfate;
[0028] Step 5, preparing a natural latex grafted lignin bioadhesive: adding the mixed solution described in step 4 to 100 parts of natural latex, stirring for 3 hours at 60±2°C and 300-330rpm to allow lignin and natural latex to undergo a grafting polymerization reaction. After the reaction is completed, unreacted macromolecular impurities are removed by filtration or centrifugation to obtain a pure adhesive product.
[0029] The present invention is described in further detail below in conjunction with embodiments:
[0030] Example 1
[0031] Step 1, prepare the 0.1 mol / L NaOH solution: add 2 g NaOH and 50 mL deionized water into a beaker, and stir with a glass rod until fully dissolved;
[0032] Step 2, preparing the 15wt% alkali lignin aqueous solution: 15 parts of alkali lignin dry powder and 85 parts of deionized water are stirred at a speed of 300-330rpm until they are completely dissolved to obtain a uniformly dispersed alkali lignin aqueous solution, and the pH thereof is adjusted to 9;
[0033] Step 3, preparing the 2 wt% ammonium persulfate solution: adding 2 parts of ammonium persulfate and 98 parts of deionized water into a beaker, stirring with a glass rod until dissolved for later use;
[0034] Step 4, preparing a mixed solution of alkali lignin and ammonium persulfate: taking 1 part of the 2wt% ammonium persulfate solution described in step 3 and 50 parts of the 15wt% alkali lignin aqueous solution described in step 2, stirring at 60±2°C and 300-330rpm for 45min to obtain a mixed solution of alkali lignin and ammonium persulfate;
[0035] Step 5, preparing a natural latex grafted lignin bioadhesive: adding the mixed solution described in step 4 to 100 parts of natural latex, stirring for 3 hours at 60±2°C and 300-330rpm to allow lignin and natural latex to undergo a grafting polymerization reaction. After the reaction is completed, unreacted macromolecular impurities are removed by filtration or centrifugation to obtain a pure adhesive product.
[0036] The natural latex grafted lignin bioadhesive prepared in this example has good coating performance, and the bonding strength reaches 206.72 N. After bonding, it is placed in an environment of 28±2°C and 70±2% relative humidity for 4 hours, and the bonding strength is still 188.29 N. After 14 days of bonding, the bonding strength can reach as high as 271.95 N. It shows its excellent water resistance and durability.
[0037] Example 2
[0038] Step 1, prepare the 0.1 mol / L NaOH solution: add 2 g NaOH and 50 mL deionized water into a beaker, and stir with a glass rod until fully dissolved;
[0039] Step 2, preparing the 15wt% sodium lignin sulfonate aqueous solution: 15 parts of sodium lignin sulfonate dry powder and 85 parts of 0.1mol / L NaOH solution are stirred at a speed of 300-330rpm until they are completely dissolved to obtain a uniformly dispersed sodium lignin sulfonate aqueous solution, and the pH thereof is adjusted to 9;
[0040] Step 3, preparing the 2 wt% ammonium persulfate solution: adding 2 parts of ammonium persulfate and 98 parts of deionized water into a beaker, stirring with a glass rod until dissolved for later use;
[0041] Step 4, preparing a mixed solution of sodium lignin sulfonate and ammonium persulfate: taking 1 part of the 2wt% ammonium persulfate solution described in step 3 and 50 parts of the 15wt% sodium lignin sulfonate aqueous solution described in step 2, stirring at 60±2°C and 300-330rpm for 45min to obtain a mixed solution of sodium lignin sulfonate and ammonium persulfate;
[0042] Step 5, preparing a natural latex grafted lignin bioadhesive: adding the mixed solution described in step 4 to 100 parts of natural latex, stirring for 3 hours at 60±2°C and 300-330rpm to allow lignin and natural latex to undergo a grafting polymerization reaction. After the reaction is completed, unreacted macromolecular impurities are removed by filtration or centrifugation to obtain a pure adhesive product.
[0043] The natural latex grafted lignin bioadhesive prepared in this example has good coating performance, and the bonding strength reaches 196.09 N. After bonding, it is placed in an environment of 28±2°C and 70±2% relative humidity for 4 hours, and the bonding strength is still 170.44 N; after 14 days of bonding, the bonding strength can be as high as 267.83 N. It shows its excellent water resistance and durability.
[0044] Example 3
[0045] Step 1, prepare the 0.1 mol / L NaOH solution: add 2 g NaOH and 50 mL deionized water into a beaker, and stir with a glass rod until fully dissolved;
[0046] Step 2, preparing the 15wt% enzymatic lignin aqueous solution: 15 parts of enzymatic lignin dry powder and 85 parts of deionized water are stirred at a speed of 300-330rpm until they are completely dissolved to obtain a uniformly dispersed enzymatic lignin aqueous solution, and the pH thereof is adjusted to 9 using the 0.1mol / LNaOH solution described in step 1;
[0047] Step 3, preparing the 2 wt% ammonium persulfate solution: adding 2 parts of ammonium persulfate and 98 parts of deionized water into a beaker, stirring with a glass rod until dissolved for later use;
[0048] Step 4, preparing a mixed solution of enzymatic lignin and ammonium persulfate: taking 1 part of the 2wt% ammonium persulfate solution described in step 3 and 50 parts of the 15wt% enzymatic lignin aqueous solution described in step 2, stirring for 45 minutes at 60±2°C and 300-330rpm to obtain a mixed solution of enzymatic lignin and ammonium persulfate;
[0049] Step 5, preparing a natural latex grafted lignin bioadhesive: adding the mixed solution described in step 4 to 100 parts of natural latex, stirring for 3 hours at 60±2°C and 300-330rpm to allow lignin and natural latex to undergo a grafting polymerization reaction. After the reaction is completed, unreacted macromolecular impurities are removed by filtration or centrifugation to obtain a pure adhesive product.
[0050] The natural latex grafted lignin bioadhesive prepared in this example has good coating performance, and the bonding strength reaches 248.32 N. After bonding, it is placed in an environment of 28±2°C and 70±2% relative humidity for 4 hours, and the bonding strength is still 188.85 N; after 14 days of bonding, the bonding strength can be as high as 269.28 N. It shows its excellent water resistance and durability.
[0051] Comparative Example
[0052] Step 1, prepare the 0.1 mol / L NaOH solution: add 2 g NaOH and 50 mL deionized water into a beaker, and stir with a glass rod until fully dissolved;
[0053] Step 2, preparing the 15wt% sodium lignin sulfonate aqueous solution: 15 parts of sodium lignin sulfonate dry powder and 85 parts of 0.1mol / L NaOH solution are stirred at a speed of 300-330rpm until they are completely dissolved to obtain a uniformly dispersed sodium lignin sulfonate aqueous solution, and the pH thereof is adjusted to 9;
[0054] Step three, prepare natural latex blended lignin bioadhesive: add 50 parts of the 15wt% sodium lignin sulfonate aqueous solution described in step two to 100 parts of natural latex, stir for 3 hours at 60±2℃ and 300-330rpm to fully mix the lignin and natural latex, and obtain the natural latex blended lignin bioadhesive.
[0055] The natural latex blended lignin bioadhesive prepared in this comparative example has good coating performance, and the bonding strength is 170.44N. After bonding, it was placed in an environment of 28±2℃ and 70±2% relative humidity for 4h, and its bonding strength was tested to be 147.14N; after 14 days of bonding, the bonding strength was only 243.46N. This shows that the adhesive prepared in this comparative example has poor bonding performance, and does not have good water resistance and durability in the absence of an initiator to graft copolymerize natural latex and lignin, and its performance is poorer than that of the above-mentioned embodiments.
[0056] Table 1 Comparison of bonding strength of the adhesives of the embodiments and comparative examples at different temperatures and humidities and after 14 days of bonding
[0057]
[0058] The methods for measuring the parameters in the above embodiments and comparative examples are as follows:
[0059] On white cardboard (400g / m 2 ) was cut into dumbbell-shaped strips, and then further cut from the middle. The adhesives prepared in the embodiments and comparative examples were mixed at 250 g / m 2 Glue coating amount and 250mm 2 The coating area is coated on the paper sample to make the two paper samples adhere together, and the sample is dried at room temperature for 20 minutes to obtain the desired sample. The bonding strength of the paper sample is measured at a speed of 10 mm / min using a universal tensile tester at room temperature, and the average value is obtained by measuring three times.
[0060] In order to verify the influence of humidity environment on the adhesive properties of the adhesives prepared in the examples and comparative examples, the prepared adhesive paper samples were placed in an environment of 28±2°C and 70±2% relative humidity for 4 hours to measure the adhesive strength of the adhesive paper samples under such conditions. In order to verify the influence of bonding time on the adhesive properties of the adhesives prepared in the examples and comparative examples, the prepared adhesive paper samples were placed in an environment of normal temperature and humidity for 14 days to measure the adhesive strength of the adhesive after 14 days of bonding.
[0061] As described above, the natural latex grafted lignin bioadhesive prepared by the present invention shows its excellent water resistance and durability. The present invention provides an environmentally friendly and high-performance natural latex grafted lignin bioadhesive and a preparation method thereof, which significantly improves the adhesive properties and water resistance of the adhesive by introducing lignin, while maintaining good biodegradability and non-toxic properties. The adhesive has broad application prospects in multiple fields and is expected to replace traditional petroleum-based adhesives and become a mainstream product in the future adhesive market.
[0062] Although the embodiments of the present invention have been disclosed above, they are not limited to the applications listed in the specification and the embodiments. It can be fully applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily realized. Therefore, without departing from the general concept defined by the claims and equivalent scope, the present invention is not limited to the specific details and the illustrations shown and described here.
Claims
1. A method for preparing a natural latex grafted lignin bioadhesive, characterized in that: The method is prepared from the following raw materials in parts by weight: 100 parts of natural rubber latex, 10 to 50 parts of 15wt% lignin solution, 1 part of 2wt% ammonium persulfate solution, and 50 mL of 0.1 mol / L NaOH solution; The preparation method of the natural latex grafted lignin bioadhesive comprises the following steps: Step 1, prepare the 0.1 mol / L NaOH solution: add 2 g NaOH and 50 mL deionized water into a beaker, and stir with a glass rod until fully dissolved; Step 2, preparing the 15wt% lignin aqueous solution: 15 parts of lignin dry powder and 85 parts of deionized water are stirred at a speed of 300-330rpm until they are completely dissolved to obtain a uniformly dispersed lignin aqueous solution, and the pH of the lignin aqueous solution is adjusted to 9 using the 0.1mol / L NaOH solution described in step 1; Step 3, preparing the 2 wt% ammonium persulfate solution: adding 2 parts of ammonium persulfate and 98 parts of deionized water into a beaker, stirring with a glass rod until dissolved for later use; Step 4, preparing a mixed solution of lignin and ammonium persulfate: taking 1 portion of the 2 wt% ammonium persulfate solution in step 3, adding it to the 15 wt% lignin aqueous solution in step 2, stirring at 60±2° C. and 300-330 rpm for 45 min to obtain a mixed solution of lignin and ammonium persulfate; Step 5, preparing a natural latex grafted lignin bioadhesive: adding the mixed solution described in step 4 to 100 parts of natural latex, stirring for 3 hours at 60±2°C and 300-330rpm to allow lignin and natural latex to undergo a grafting polymerization reaction. After the reaction is completed, unreacted macromolecular impurities are removed by filtration or centrifugation to obtain a pure adhesive product.
2. The method for preparing the natural latex grafted lignin bioadhesive according to claim 1, characterized in that: The weight proportion of lignin in the lignin aqueous solution is 15%.
3. The method for preparing the natural latex grafted lignin bioadhesive according to claim 1, characterized in that: In the step 4, the stirring time of the mixed solution of lignin and ammonium persulfate is 45 minutes, and the reaction temperature is 60±2°C.
4. The method for preparing the natural latex grafted lignin bioadhesive according to claim 1, characterized in that: The reaction time in step 5 is 3 h and the reaction temperature is 60±2° C.
5. The method for preparing the natural latex grafted lignin bioadhesive according to claim 1, characterized in that: The lignin in step 2 is one or more of alkali lignin, sodium lignin sulfonate, and enzymatic lignin.
Citation Information
Cited By
Environment-friendly insole adhesive and preparation method thereof
CN121022345A
An environmentally friendly shoe insole adhesive and its preparation method
CN121022345B